The Effect Of The Contextual Teaching Learning (CTL) Learning Model On The Mathematics Learning Outcomes Of Grade III Students - Pakpahan, Saulina; Sitio, Hetdy; Sibarani, Imelda Sabrina (CV Putra Publisher, 2025)
Contextual Teaching Learning (CTL), Mathematics, Learning Results The aim of this research is to determine the effect of the Talking Stick learning model on Mathematics learning outcomes in class V students at UPTD SD Negeri 122399 Pematangsiantar. The type of research used in this research is quantitative research. The research design that will be used is an experiment, in the form of Pre- experimental Design which uses a